The Role of P4HA1 in Multiple Cancer Types and its Potential as a Target in Renal Cell Carcinoma - Li, Yang; Ge, Yu-Zheng; Qian, Yiguan; Chen, Ke; Zhao, Feng; Qin, Zhiqiang; Zhou, Liuhua; Xu, Luwei; Xu, Zheng; Dou, Quanliang; Jia, Ruipeng (Frontiers in Genetics, 2022)
Background: Prolyl 4-hydroxylase subunit alpha 1 (P4HA1) provides the majority of the catalytic site of the active P4H enzyme. Emerging evidence has revealed that P4HA1 participates in the initiation and development of several malignant tumors. However, a pan-cancer analysis of P4HA1 has not been performed. Methods: In this study, we carried out an in-depth analysis of the expression patterns and prognostic value of P4HA1 using the datasets of The Cancer Genome Atlas and Kaplan-Meier Plotter. Genomic and epigenetic alterations of P4HA1 and the correlation of P4HA1 with immune infiltration and DNA methylation in different cancers were also analyzed across multiple databases. We also further explored the biological function and mechanism of P4HA1 in renal cell carcinoma (RCC). Results: We characterized the expression profiles and prognostic values of P4HA1 in multiple cancer types. P4HA1 expression was increased in clear cell RCC compared to adjacent normal tissues, and P4HA1 positively correlated with overall survival (OS) and disease-free survival (DFS) in papillary RCC. In addition, a positive correlation between P4HA1 expression and immune cell infiltration was observed in clear cell RCC. We also identified a strong correlation between P4HA1 expression and immune checkpoint gene expression, microsatellite instability, and tumor mutation burden in chromophobe RCC. Finally, the results of in vitro experiments verified that overexpression of P4HA1 promoted the proliferation, migration, invasion, and epithelial–mesenchymal transition of RCC cells. Conclusion: Overall, our study suggested that P4HA1 might play a significant role in tumorigenesis in RCC and may be a prognostic biomarker and therapeutic target for several malignant tumors, including RCC.